Phytochemicals and bioactivity of Piper porphyrophyllum N. E. Br. and Piper sarmentosum Roxb. [electronic resource] - Raihan Murni Sidek, 1986- (2013)
Thesis (Sarjana Sains (Kimia)) - Universiti Teknologi Malaysia, 2013